Application of dicarbamin in treatment of patients by a chronic hepatitis C - D. Yu. Konstantinov; Ye. A. Konstantinova; L. L. Popova; E. A. Strebkova; A. A. Suzdaltsev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2011)
Aim of investigation. Studying of clinical and laboratory efficacy of dicarbamin as hematoprotector in patients with chronic hepatitis C (CHC) with 1b virus genotype at combined antiviral therapy (AVT) by pegilated interferons in combination to ribavirin.Material and methods. Overall 110 patients with CHC (genotype 1b) with WBC count from 3,9 to 3,0×109/l and neutrophile count from 2,0 to 1,5×109/l according to TBC were under surveillance. Patients were divided to comparable groups by gender and age in relation to the treatment mode: the 1-st group (n=52) received peginterferon α2b + ribavirin, the 2-nd group (n=58) – peginterferon α2b + ribavirin + dicarbamin 100 mg od for 21 day. Subsequently dicarbamin was prescribed to all patients in the similar mode for 3 months.Results. At combined AVT no undesirable effects as decrease of total leukocyte and neutrophile count were revealed. In the 1-st group leukopenia was observed from the 4-th week of treatment in 71%, neutropenia – in 69% of patients, similar parameters kept significantly lower during the whole course of treatment in comparison to the 2-nd group that resulted in dose decline of peginterferon α2b in 26,9% and cancellation of AVT in 9,6% of patients. At patients of the 2-nd group leukopenia was marked in 35%, neutropenia – in 46% of cases. No significant reduction of leukocyte and neutrophile count which could cause correction of dose or cessation of AVT has not been registered in this group.Conclusions. Application of dicarbamin at combined antiviral therapy of CHC results in elevation of leukocyte and neutrophile count in the blood and allows to carry out treatment without dose decline and cancellation of peginterferon. High tolerability of AVT in CHC patients at application of suggested mode of treatment (peginterferon α2b, ribavirin and dicarbamin) was revealed.